Dolor Pélvico Crónico - Cordero Luján, Raymundo; Laguna Suárez, Eduardo; Llanos Z., Roberto; Baccini, Javier (Revista Peruana de Ginecología y Obstetricia, 2015)
Dolor Pélvico Crónico - Fisiopatología, Diagnóstico, Aspectos psicológicos, Prevención y tratamiento.